A randomized trial on the efficacy of split-body versus full-body resistance training in non-resistance trained women - Helene Pedersen; Marius Steiro Fimland; Brad J. Schoenfeld; Vegard Moe Iversen; Kristoffer Toldnes Cumming; Susanne Jensen; Atle Hole Saeterbakken; Vidar Andersen (BMC, 2022)
Abstract Background The aim of this study was to assess the efficacy of a 12-week upper/lower split- versus a full-body resistance training program on maximal strength, muscle mass and explosive characteristics. Fifty resistance untrained women were pair-matched according to baseline strength and randomized to either a full-body (FB) routine that trained all of the major muscle groups in one session twice per week, or a split-body program (SPLIT) that performed 4 weekly sessions (2 upper body and 2 lower body). Both groups performed the same exercises and weekly number of sets and repetitions. Each exercise was performed with three sets and 8-12 repetition maximum (RM) loading. Study outcomes included maximal strength, muscle mass, jump height and maximal power output. Results No between-group differences were found in any of the variables. However, both FB and SPLIT increased mean 1-RM from pre- to post-test in the bench press by 25.5% versus 30.0%, lat pulldown by 27.2% versus 26.0% and leg press by 29.2% versus 28.3%, respectively. Moreover, both FB and SPLIT increased jump height by 12.5% versus 12.5%, upper-body power by 20.3% versus 16.7% and muscle mass by 1.9% versus 1.7%, p < 0.01, respectively. Conclusions This study did not show any benefits for split-body resistance-training program compared to full-body resistance training program on measures of maximal- and explosive muscle strength, and muscle mass. Trial registration: ISRCTN81548172, registered 15. February 2022.